Long-term activation of the pro-coagulant response after neoadjuvant chemoradiation and major cancer surgery. - PIDGEON, GRAHAM; REYNOLDS, JOHN; MAHER, STEPHEN; WHITE, BARRY; O'DONNELL, JAMES (My University, 2010)
Background: The association between cancer, major surgery and venous thromboembolism (VTE) is well established. Multimodal therapy is increasingly being used as standard treatment for localised gastrointestinal cancer. The aim of this study was to examine the markers of pro-coagulation response and VTE risk in an exemplar multimodal model of pre-operative combination chemotherapy and radiation therapy, followed by complex cancer surgery. Methods: Consecutive patients (n=36) with localised oesophageal cancer were studied at baseline after the first and second cycles of chemoradiation, and on post-operative days 1?28, and at 3, 6 and 9 months. Factors regulating the pro- and anti-coagulant response, as well as pro-inflammatory markers including NF?B activation in peripheral blood mononuclear cells, were examined. All patients received enoxaparin 40?mg s.c. postoperatively up to discharge, and underwent pulmonary CT-pulmonary angiography and venography on day 10 postoperatively. Results: Four (11%) non-fatal thromboembolic events were documented, all after hospital discharge. Neoadjuvant therapy before surgery activated factor VIII (FVIII) and pro-inflammatory NF?B, and increased D-dimers, pro-thrombin fragment 1+2 (F1+2) and the thrombin-anti-thrombin complex (TAT). Surgery significantly (P<0.05) increased pro-thrombin time (PT), activated partial thromboplastin time, fibrinogen, D-dimers, TAT, F1+2 and FVIII up to 6 months. Conclusion: These data highlight the linked pro-coagulant and immunoinflammatory pathways in the multimodal management of oesophageal cancer, and suggest that the duration of current standard thromboprophylaxis regimens warrants further study.
PUBLISHED
Keywords: Oncology; Surgery; oesophageal cancer; Cancer